Managing operations across the supply chain (McGraw-Hill Education, 2011)
Managing Operations Across the Supply Chain is the first book to offer a global, supply chain perspective of operations management – a treatment that embraces the foundations of operations management but includes new frameworks, concepts, and tools to address the demands of today and changing needs of the future. It reflects three key shifts in operations management